Моделі міжз‘єднань компонентів комп‘ютерних систем - Кудря, Володимир Григорович (НТУ "ХПІ", 2015)
Виконано дослідження способів інтерпретації мережі міжз‘єднань високочастотної, в тому числі і нанотехнологічної електроніки. Системний спосіб їх подання у вигляді синтезу польової та ланцюгової структури дозволив розробити теоретичне обґрунтування схемотехнічного зображення електромагнітних процесів провідників, що утворюють комунікативну мережу компонентів, що виконують локальні функціональні перетворення. Отримані макромоделі міжз’єднань, що дозволяють виконувати оцінки впливу, як внутрішніх, так і зовнішніх позасистемних електромагнітних перешкод. Результати дослідження спрямовані на підвищення ефективності проектування засобів інформаційно комунікаційних технологій.

A sudden jump in production technology of computer systems and their components, in the opinion of the author, found a world civilization unprepared for its effective use and scientific-theoretical substantiation of a number of technological problems. One of these problems is the actual physical construction of mathematical models that reflect the synergistic nature of the process, the operation of modern monolithic integrated circuits. In particular, the problem of adequate reflection of the network connections between the component becomes an obstacle to increasing the speed of data processing and further sealing valve and transistor elements per unit volume. This paper has explored ways of interpreting high-frequency interconnect network, including nanotechnology and electronics. Systematic way of presenting the device in a field and a chain structure allowed to develop theoretical grounding circuit processes image electromagnetic conductors that form a communicative network components. The methods of constructing models of interconnects allow assessment of the impact, both internal and external exogenous electromagnetic interference. The results of research aimed at improving design of information and communication technologies.
Model interconnect components computer system
Keywords: високочастотна електроніка; моделі електромагнітних перешкод; комунікатор; закони Кірхгофа; high-frequency electronics; electromagnetic interference models; MEMS